2014
DOI: 10.1039/c4sc01348d
|View full text |Cite
|
Sign up to set email alerts
|

Conformationally strained trans-cyclooctene with improved stability and excellent reactivity in tetrazine ligation

Abstract: Computation has guided the design of conformationally-strained dioxolane-fused trans-cyclooctene (d-TCO) derivatives that display excellent reactivity in the tetrazine ligation. A water soluble derivative of 3,6-dipyridyl-s-tetrazine reacts with d-TCO with a second order rate k2 366,000 (+/− 15,000) M−1s−1 at 25 °C in pure water. Furthermore, d-TCO derivatives can be prepared easily, are accessed through diastereoselective synthesis, and are typically crystalline bench-stable solids that are stable in aqueous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
351
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 241 publications
(362 citation statements)
references
References 70 publications
(122 reference statements)
10
351
0
1
Order By: Relevance
“…We focused on bioorthogonal IEDAC reactions because of their fast reaction rates (up to 10 6 M −1 s −1 ) 66,67 and excellent biocompatibility. In this regard, we chose UAAs bearing strained alkyne or alkene functionalities (Figure 2A), including 1,3-disubstituted cyclopropene-lysine (CpK), 68 bicyclo[6.1.0]nonyne-lysine (BCNK), 54,69 trans -cyclooct-4-ene-lysine (4’-TCOK), 51,54 and axial trans -cyclooct-2-ene-lysine (2’-aTCOK), 55,70,71 all of which can be site-specifically incorporated into proteins expressed in mammalian cells using variants of the pyrrolysyl-tRNA synthetase (PylRS)/Pyl-tRNA CUA pair and react with tetrazines chemoselectively.…”
Section: Resultsmentioning
confidence: 99%
“…We focused on bioorthogonal IEDAC reactions because of their fast reaction rates (up to 10 6 M −1 s −1 ) 66,67 and excellent biocompatibility. In this regard, we chose UAAs bearing strained alkyne or alkene functionalities (Figure 2A), including 1,3-disubstituted cyclopropene-lysine (CpK), 68 bicyclo[6.1.0]nonyne-lysine (BCNK), 54,69 trans -cyclooct-4-ene-lysine (4’-TCOK), 51,54 and axial trans -cyclooct-2-ene-lysine (2’-aTCOK), 55,70,71 all of which can be site-specifically incorporated into proteins expressed in mammalian cells using variants of the pyrrolysyl-tRNA synthetase (PylRS)/Pyl-tRNA CUA pair and react with tetrazines chemoselectively.…”
Section: Resultsmentioning
confidence: 99%
“…Future work could explore whether similar masking effects occur for different hydrophobic reactants such as DBCO, norbornene, and methyl-cyclopropene, alternative linkers directly distal to the TCO such as those containing bulky phenyl groups, 16 or new bicyclic TCO derivatives that have faster reaction rates, greater stability, and, for the dioxolane-fused TCO, potentially greater hydrophilicity. 46,47 Expanding these investigations to different types of proteins or biological molecules, including site-specific methods that involve genetic encoding, 48-50 would also be of interest.…”
Section: Resultsmentioning
confidence: 99%
“…31 With strained trans -cyclooctenes, we have measured bimolecular rate constants as high as 3.3 × 10 6 M −1 s −1 in reactions with tetrazines (Tz), representing the fastest bioorthogonal reactions reported to date. 32,33 Tetrazines are typically synthesized through the chemical oxidation of dihydrotetrazine (DHTz) precursors, 34 and the electroactivity of tetrazines is well established. 35 Recently, Devaraj has demonstrated that electrochemistry can be used to control the redox state of pendant DHTz/Tz groups on the surface of microelectrodes, allowing selective bioconjugation to oxidized electrode surfaces.…”
Section: Introductionmentioning
confidence: 99%